Analisis Pelanggaran Hak Asasi Manusia (HAM) Dalam Sengketa Wilayah Perbatasan Kashmir - Rizki, Khairur; Muquita, Namira Risqi Putri (Universitas Komputer Indonesia, 2023)
This paper aims to show human rights violations that occurred in the Kashmir border area. Kashmir is a disputed area in South Asia between India and Pakistan. The dispute occurred due to complex historical factors that led to conflict between the Indian government and the Kashmiri Muslim community. For Kashmiri Muslims, the Kashmir region is not only a place of origin but also representing social structure and identity. The escalation of the conflict also triggering persecution toward Kashmiri Muslims led to protests in various forms. Protests and demonstrations were also carried out because of the many human rights violations committed by the Indian government against the Kashmiri Muslim community. Human rights violations also continue to occur to the Kashmiri community who protest. This paper uses one theory and one concept, the conflict theory by Karl Marx to explain the conflicts that occurred and the concept of Human Rights to analyze the various human rights violations that occurred. The results of this study indicate that the Kashmiri Muslim community has experienced various human rights violations committed by the Indian authorities. Keywords: Conflict, Human Rights Violation, India, Kashmir, Pakistan